Knowledge of attention-deficit hyperactivity disorder among the general public, parents, and primary school teachers. Issue 12 (26th March 2021) - See, Lai-Chu; Li, Hsin-Mei; Chao, Kuo-Yu; Chung, Chia-Chi; Li, Pei-Ru; Lin, Sheue-Rong
Abstract : Abstract: We compared the knowledge of attention-deficit hyperactivity disorder (ADHD) among the general public, parents of children with ADHD, and primary school teachers and identified factors associated with ADHD knowledge in each group, separately. Secondary data analysis was made on the pre-lecture data from those (122 from the general public, 64 parents of children with ADHD, and 515 primary school teachers) attending education lectures by the Department of Public Health, New Taipei City Government, Taiwan, 2014. ADHD onset age was least known in these 3 groups. Knowledge of ADHD was significantly better among teachers (test score, 75.3%) than among parents (65.5%) and the general public (59.2%). Among the general public, the test score significantly decreased with age and was worst in those who did not know their friends or relatives with ADHD. Among parents, service workers, and retired/unemployed knew significantly less about ADHD than housewife did. Among teachers, men knew significantly less than women; those who taught children with ADHD knew significantly more than those who did not. Primary school teachers knew more about ADHD than parents and the general public. Factors associated with ADHD knowledge varied among the 3 groups.